Purification and properties of acid phosphatase (EC 3.1.3.2) secreted by strain 74A of the mould Neurospora crassa - Han, S. W.; Rossi, A. (Rapid Science Publishers, 1996)
Both P-i-repressible acid phosphatases, IIb (mycelial) and IIc (extracellular), synthesized by Neurospora crassa and purified to apparent homogeneity by 7.5% PAGE, are monomers, are inhibited by 2 mM ZnCl2 and are nonspecifically stimulated by salts. However, the IIc form is activated by p-nitrophenylphosphate (in a negative cooperativity effect with a K-0.5 of 2.5 mM) whereas form IIb shows Michaelis kinetics, with a K-m of 0.5 mM. Thus, since both enzymatic forms may be expressed by the same gene (pho-3), it is possible that post-translational modifications lead to the excretion of an enzymatic form with altered Michaelis kinetics compared with the enzymatic form retained by the mycelium.
Keywords: acid phosphatase; enzyme secretion; fungi; Neurospora crassa; phosphate regulation